2018
DOI: 10.1016/j.chempr.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Highly Fluorinated Interphases Enable High-Voltage Li-Metal Batteries

Abstract: Li metal is regarded as the ''Holy Grail'' electrode because of its highest specific capacity and lowest electrochemical potential. However, challenges arising from the low Coulombic efficiency (CE) and dendritic nature of Li metal in carbonate electrolytes remain to be resolved. Here, by increasing LiFSI salt concentration in the carbonate electrolyte, we successfully increased the CE to 99.3% while suppressing Li dendrite formation. An NMC622jjLi cell was paired and showed excellent cycling performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
661
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 764 publications
(680 citation statements)
references
References 55 publications
(73 reference statements)
19
661
0
Order By: Relevance
“…Although graphite carbon holds the main market of anodic materials in commercial LIBs due to its cycling stability, the low theoretical capacity (372 mAh g −1 , LiC 6 ) hinders its further development and applications in high‐energy LIBs . Lithium metal (LM) is a promising anode material because of the high theoretical specific capacity (3860 mAh g −1 ), however, the safety issue and the uncontrollable Li dendrites growth are still difficult to overcome . Comparing with lithium metal, the intercalation‐type silicon (Si) anode affords an even higher theoretical specific capacity (4200 mAh g −1 , Li 4.4 Si) with accommodating over 4 Li + per Si .…”
Section: Introductionmentioning
confidence: 99%
“…Although graphite carbon holds the main market of anodic materials in commercial LIBs due to its cycling stability, the low theoretical capacity (372 mAh g −1 , LiC 6 ) hinders its further development and applications in high‐energy LIBs . Lithium metal (LM) is a promising anode material because of the high theoretical specific capacity (3860 mAh g −1 ), however, the safety issue and the uncontrollable Li dendrites growth are still difficult to overcome . Comparing with lithium metal, the intercalation‐type silicon (Si) anode affords an even higher theoretical specific capacity (4200 mAh g −1 , Li 4.4 Si) with accommodating over 4 Li + per Si .…”
Section: Introductionmentioning
confidence: 99%
“…[1] In spite of these advantages, a substantial gap remains before practical application due to vulnerable dendritic growth during repeated Li deposition and stripping. [10][11][12][13] In the case of artificial SEI layers, while their effect is noticeable in the early cycling period, inevitable Lithium metal has been hailed as a key enabler of upcoming rechargeable batteries with high energy densities. One is the "space charge" model.…”
mentioning
confidence: 99%
“…[12] Qian et al [13] first demonstrated that ether-based HCEs indeed significantly suppress dendritic growth and achieve high Coulombic efficiencies (CEs; >97%). Moreover, high Li ion concentrations in HCEs delay the onset point of ion depletion to a higher current density and could thus alleviate dendrite growth markedly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, chemistry of SEI layer also depends on the concentration of lithium salt by modulating the reductive stability of salt anions and solvents. Wang's group obtained a fluorinated interphase in concentrated carbonate electrolyte with about 10 M LiFSI salt . This F‐rich layer contributed to dendrite‐free surface and desirable efficiency over 99 %.…”
Section: Liquid Electrolytesmentioning
confidence: 99%